Intestinal parasites and commensals among individuals from a landless camping in the rural area of Uberlândia, Minas Gerais, Brazil - Maria Cecília Oliveira; Claudio Vieira da Silva; Julia Maria Costa-Cruz (Universidade de São Paulo (USP), 2003)
We evaluated the occurrence of intestinal parasites and commensals among children and adults from a landless camping in the rural area of Uberlândia, State of Minas Gerais, Brazil, from October to November 2001. Stool samples from 78 individuals were examined by both the Baermann-Moraes and Lutz methods. Fifty-one (65.4%; CI 54.8 - 76.0) individuals were found to be infected, 23 (45.1%) children and 28 (54.9%) adults, of whom 34 (66.7%) were mono-infected, 9 (17.6%) bi-infected, and 8 (15.7%) poly-infected. In conclusion, the high prevalence of intestinal parasites and commensals suggests that parasitological exams should be periodically carried out in addition to the sanitation education and health special care in this population.